Under-canopy afforestation after 10 years: assessing the potential of converting monoculture plantations into mixed stands - Gao, Yuan; Zhang, Zhidong; Lu, Deliang; Zhou, Ying; Liu, Qiang (Frontiers in Plant Science, 2024)
Under-canopy afforestation using different tree species is a key approach in close-to-nature management to improve the structural and functional stability of plantation forests. However, current research on understory afforestation mainly focuses on the seedling stage, with limited attention to saplings or young trees. In this study, we evaluated the growth characteristics and leaf traits of 14-year-old Pinus sylvestris var. Mongolica trees under four different upper forest density (UFD) treatments: 0 trees/hm 2 (canopy openness 100%, CK), 150 trees/hm 2 (canopy openness 51.9%, T1), 225 trees/hm 2 (canopy openness 43.2%, T2), and 300 trees/hm 2 (canopy openness 28.4%, T3). We found that the survival rate of P. sylvestris in the T3 was significantly lower than in the other treatments, with a decrease of 30.2%, 18.3%, and 19.5% compared to CK, T1, and T2, respectively. The growth of P. sylvestris in the T1 treatment exhibited superior performance. Specifically, T1 showed a significant increase of 18.8%, 5.5%, and 24.1% in tree height, diameter at breast height, and crown width, respectively, compared to the CK. The mean trunk biomass ratio in the understory was significantly higher than that in full light by 15.4%, whereas the mean leaf biomass ratio was significantly lower by 12.3%. Understory P. sylvestris trees tended to allocate more biomass to the trunk at the expense of decreasing leaf biomass, which would facilitate height growth to escape the shading environment, although the promotion was relatively limited. Leaf length, leaf width, leaf area, leaf thickness, mesophyll tissue thickness, epidermis thickness, and leaf carbon content were the highest in the CK and tended to decrease with increasing UFD, indicating that a high-light environment favored leaf growth and enhanced carbon accumulation. In summary, young P. sylvestris trees adapted to moderate shading conditions created by the upper canopy, and the T1 treatment was optimal for the growth of understory P. sylvestris.This study provides insights into different adaptive strategies of young P. sylvestris trees to 2 changes in light environment, providing practical evidence for under-canopy afforestation using light-demanding trees during pure plantation transformation.